Android theft guard - Chew, Wee Han (2015)
Today, mobile phones have become a necessity tool in our everyday life. With the innovation in the technology advancement, it is no longer just a basic communication gadget but a computation device. Since mobile phones are so convenient now, many users have stored their sensitive and confidential data on their phones. To those whom are working under confidential companies losing their phone may imposed severe threat to them, while there is a high chance that important information might leaked out. Hence, it is important to protect these data and to enhance the security of mobile phones. This project aims to develop an Anti-Theft application on Android devices and mobile phones. PicMeNavi has been successfully developed via Android platform. This application features comprises of retrieving lost or stolen mobile phone location, snapping of theft pictures, sending theft alert notification emails along with the picture taken and invoking the alarm of the Android device remotely. In addition, PicMeNavi is even capable of tracking the stolen phone when the theft attempts to change the sim card. A text message together with the new number will be send to the user recovery number upon the stolen phone reboots. With the use of SMS control, user is able to retrieve all this information anytime in an erase. Based on the comparison of related Android Anti-Theft application. The functionality and flexibility of PicMeNavi stands out to be uniquely as compared to these application. Most Anti-Theft application are usually controlled with a web base server where user will only be able to retrieve their lost phone information through this website. There are also sequence of procedures for user to follow before they could start to use the Anti-Theft application. However, PicMeNavi does not require this any complicated procedures to retrieve these information. To reduce the complexity of using this application, user will only need to use some SMS command as an authentication to track the lost mobile phone. Lastly, this application will not trigger the alertness of the theft as all the features will be running remotely and programmatically.